Treatment outcomes for methamphetamine users receiving outpatient counselling from the Stimulant Treatment Program in Australia - McKetin, Rebecca; Dunlop, A.; Holland, R.; Sutherland, R.; Baker, A.; Salmon, A.; Hudson, S. (Wiley-Blackwell Publishing Ltd., 2013)
Introduction and Aims. The purpose of this study was to document treatment outcomes for methamphetamine users receiving outpatient counselling from the Stimulant Treatment Program (STP) in Australia. Design and Methods. Clients attending the STP for methamphetamine use (n=105) were assessed on entry to the service and at 3 (n=86) and 6months (n=83) after starting treatment. At each interview methamphetamine use (days of use, severity of dependence), other drug use and health and social functioning (HIV risk behaviour, crime, disability, psychotic symptoms and hostility) were assessed for the past month. Results. Participants received a median of six counselling sessions (interquartile range 1-11) over a period of 89days (interquartile range 41-148days). Past month methamphetamine use fell from 79% at treatment entry to 53% at the 3-month follow-up (P < 0.001) and 55% at the 6-month follow-up (P < 0.001). There were statistically significant reductions in psychotic symptoms, hostility and disability associated with poor mental health. There was no change in other drug use, crime or HIV risk behaviour. Reductions in methamphetamine were more common among younger participants, those who had no history of drug treatment and those without concurrent heroin use. Discussion and Conclusions. Methamphetamine users entering the STP showed reductions in methamphetamine use and improvements in their mental health after treatment. Improved treatment responses are needed to address polydr ug use and other harms within in this population.[McKetin R, Dunlop AJ, Holland RM, Sutherland RA, Baker AL, Salmon AM, Hudson SL. Treatment outcomes for methamphetamine users receiving outpatient counselling from the Stimulant Treatment Program in Australia.